Implementasi Pembelajaran Blended Learning Dalam Meningkatkan Hasil Belajar Siswa - Simamora, Anni Theresia (JURNAL GLOBAL EDUKASI, 2022)
Abstract: This research is motivated by the Covid-19 pandemic in Indonesia has entered a new normal era, especially in the field of education. Where new normal ers have new habits in carrying out learning, such as online learning (distance). Whereas previously schools avoided industrial technology-based learning. limited learning time causes the learning process to be less effective because the material in the subjects is quite dense, especially in Social Studies (IPS) lessons, so that not all subject matter can be fully explained optimally optimally. So from there are many learning methods that researchers see, researchers choose one model from the umpteenth of many learning models, namely the Blended learning model (online and face-to-face mixed learning models) as an alternative solution that can be used so that learning outcomes increase. From the data found by researchers in the field, it can be concluded that the use of the Blended learning model can improve student activities and learning outcomes (Cognitive, Affective, and Psychomotor Domains) of students in the classroom.Keywords: blended learning; effective; learning outcomesAbstak: Penelitian ini dilatarbelakangi oleh pandemi Covid-19 di Indonesia telah memasuki era new normal khusunya di bidang pendidikan. Dimana era new normal memiliki kebiasan baru dalam melaksanakan pembelajaran, seperti pembelajaran secara daring (jarak jauh). Padahal sebelumnya sekolah menghindari pembelajaran berbasis teknologi industri. waktu pembelajaran yang terbatas menyebabkan proses pembelajaran menjadi kurang efektif karena materi-materi pada mata pelajaran cukup padat khususnya pada pelajaran Ilmu Pengetahuan Sosial (IPS), sehingga tidak semua materi pelajaran dapat tuntas dijelaskan secara optimal maksimal. Maka dari ada banyak metode pembelajaran yang peneliti lihat maka peneliti memilih salah satu model dari kesekian banyak model pembelajara yaitu model Blended learning (model belajar campuran secara daring dan tatap muka) sebagai alternatif solusi yang dapat digunakan agar hasil belajar meningkat. Dari data yang ditemukan peneliti dilapangan maka dapat disimpulkan bahwa penggunaan model Blended learning dapat meningkatkan aktivitas dan hasil belajar siswa (Ranah Kognitif, Afektif, dan Psikomotorik) siswa di kelasKata kunci: blended learning; efektif; hasil belajar